Availability of Rehabilitation Programmes in Correctional Facilities in Southwestern Nigeria - Makinde, Wasiu (Journal of Public Policy and Administration, 2023)
Purpose: The study examined the availability and adequacy of rehabilitation programmes in Nigeria Correctional Facilities. Methodology: A study of sampled Correctional Facilities in Southwestern Nigeria, aimed at using on-site observation for availability of rehabilitation programmes as well as ascertaining the adequacy of such rehabilitation programmes in those sampled correctional facilities. Descriptive research design through observation and administration of questionnaire as well as interviewed was used to extract relevant data for the study. Findings: The study discovered that there are various rehabilitation programmes such as recreational activities, adult literacy, educational programmes, counselling programmes, among others which are adequately provided to rehabilitate inmates and prepare them for life after incarceration. Unique Contribution to Theory, Practice and Policy: The study concluded that the rehabilitation programmes available need to be strengthened especially in the area of after care service so that there will be adequate support to start what was learned after incarceration.